Impact of dietary nitrate on age‐related diastolic dysfunction. (26th April 2016) - Rammos, Christos; Hendgen‐Cotta, Ulrike B.; Totzeck, Matthias; Pohl, Julia; Lüdike, Peter; Flögel, Ulrich; Deenen, René; Köhrer, Karl; French, Brent A.; Gödecke, Axel; Kelm, Malte; Rassaf, Tienush
Abstract: Aims: Diastolic dysfunction is highly prevalent, and ageing is the main contributor due to impairments in active cardiac relaxation, ventriculo‐vascular stiffening, and endothelial dysfunction. Nitric oxide (NO) affects cardiovascular functions, and NO bioavailability is critically reduced with ageing. Whether replenishment of NO deficiency with dietary inorganic nitrate would offer a novel approach to reverse age‐related cardiovascular alterations was not known. Methods and results: A dietary nitrate supplementation was applied to young (6 month) and old (20 month) wild‐type mice for 8 weeks and compared with controls. High‐resolution ultrasound, pressure–volume catheter techniques, and isolated heart measurements were applied to assess cardiac diastolic and vascular functions. Cardiac manganese‐enhanced magnetic resonance imaging was performed to study the effects of dietary nitrate on myocyte calcium handling. In aged mice with preserved systolic function, dietary nitrate supplementation improved LV diastolic function, arterial compliance, and coronary flow reserve. Mechanistically, improved cardiovascular functions were associated with an accelerated cardiomyocyte calcium handling and augmented NO/cyclic guanosine monophosphate/protein kinase G signalling, while enhanced nitrate reduction was related to age‐related differences in the oral microbiome. Conclusion: Dietary inorganic nitrate reverses age‐related LV diastolic dysfunction and improves vascular functions. Our results highlight the potential of a dietary approach in the therapy of age‐related cardiovascular alterations.